2012
DOI: 10.1016/j.celrep.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD133 by HDAC6 Promotes β-Catenin Signaling to Suppress Cancer Cell Differentiation

Abstract: SUMMARY The pentaspan membrane glycoprotein CD133 marks lineage-specific cancer progenitor cells and is associated with poor prognosis in a number of tumor types. Despite its utility as a cancer progenitor cell marker, CD133 protein regulation and molecular function remain poorly understood. We find that the deacetylase HDAC6 physically associates with CD133 to negatively regulate CD133 trafficking down the endosomal-lysosomal pathway for degradation. We further demonstrate that CD133, HDAC6, and the central m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 47 publications
7
166
0
Order By: Relevance
“…In the present study, although TSA enhanced the transcription level of β-catenin in BGC-823 and MCF-7 cells, the protein levels were reduced following TSA treatment (Fig. 5), which was consistent with previous studies reporting that HDAC6 is required for β-catenin activation in colon cancer cells (20,21). Whether TSA-mediated EMT induction and inhibition, elevation of β-catenin mRNA levels and inhibition of β-catenin protein levels are associated with other signaling pathways, such as the decorin-β-catenin-E-cadherin signaling pathway (22), remains unclear and is currently under investigation.…”
Section: Tsa Increases the Expression Levels Of Mesenchymal Markers Asupporting
confidence: 82%
“…In the present study, although TSA enhanced the transcription level of β-catenin in BGC-823 and MCF-7 cells, the protein levels were reduced following TSA treatment (Fig. 5), which was consistent with previous studies reporting that HDAC6 is required for β-catenin activation in colon cancer cells (20,21). Whether TSA-mediated EMT induction and inhibition, elevation of β-catenin mRNA levels and inhibition of β-catenin protein levels are associated with other signaling pathways, such as the decorin-β-catenin-E-cadherin signaling pathway (22), remains unclear and is currently under investigation.…”
Section: Tsa Increases the Expression Levels Of Mesenchymal Markers Asupporting
confidence: 82%
“…Caco-2 cells can differentiate into an enterocyte-like phenotype, either with treatment by HDAC inhibitors or spontaneously with overconfluence, characterized by a polarized monolayer and the expression of cytokeratin 20 (KRT20) and the brush-border enzymes such as sucrase-isomaltase (SI). 21,22 To determine whether βHB has a role in human intestinal cell differentiation, Caco-2 cells were treated with βHB for 48 h and the mRNA levels of the enterocyte markers SI and KRT20 were determined. As shown in Figure 1a, treatment of Caco-2 cells with βHB-induced SI and KRT20 mRNA expression, suggesting that βHB increases enterocyte differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Besides histones, p300 catalyses many nonhistone proteins, including β-catenin (Wolf et al, 2002). Indeed, Li et al reported that acetylation at Lysine 49 was required for β-catenin phosphorylation (Li et al, 2008), whereas downregulation of histone deacetylation resulted in β-catenin degradation in colon cancer cells Mak et al, 2012).…”
Section: Discussionmentioning
confidence: 99%